2014
DOI: 10.4995/ijpme.2014.2326
|View full text |Cite
|
Sign up to set email alerts
|

Enterprise Modeling in the context of Enterprise Engineering: State of the art and outlook

Abstract: Enterprise Modeling is a central activity in Enterprise Engineering which can facilitate Production Management activities. This state-of-the-art paper first recalls definitions and fundamental principles of enterprise modelling, which goes far beyond process modeling. The CIMOSA modeling framework, which is based on an event-driven process-based modeling language suitable for enterprise system analysis and model enactment, is used as a reference conceptual framework because of its generality. Next, the focus i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Events describe a change in state before or after execution, which implies an action such as the start of a business process or activity (Vernadat, 2014).…”
Section: Preliminariesmentioning
confidence: 99%
See 1 more Smart Citation
“…Events describe a change in state before or after execution, which implies an action such as the start of a business process or activity (Vernadat, 2014).…”
Section: Preliminariesmentioning
confidence: 99%
“…In the SAP ERP RMs, the business process model uses EPCs, which represent sequences of events and activities. Recently, the EPC notation has been replaced by business process modeling notation (Vernadat, 2014). Gulledge et al (2004) indicated that the business processes within the SAP ERP are defined as levels such as enterprise area, scenario, process group, and process.…”
Section: Sap Erp Rms: a Case Studymentioning
confidence: 99%
“…Indeed, Interoperability is a systemic concept by nature: it is about systems that interact [28], [29], [30]. In addition, having a systemic view is very important and widely used in enterprise modelling because it provides a component-oriented view, which reflects closely the reality of enterprise systems' functioning [31], [32], [33].…”
Section: Introductionmentioning
confidence: 99%
“…This procurement is well aligned with the proposal of Ocampo and Ocampo (2015), "Developing initiatives that simultaneously enhance customer satisfaction and community development by addressing environmental concerns on toxic substance, GHG emissions and air emissions is fundamentally important to increase revenue and profit.". Moreover, Vernadat (2014) states that successful management delves with making sure that the processes are executed in such a way that business objectives are achieved in an efficient, effective and economic way.…”
Section: Introductionmentioning
confidence: 99%